Biased and inflexible interpretations of ambiguous social situations: Associations with eating disorder symptoms and socioemotional functioning. Issue 4 (7th February 2022) - Bronstein, Michael V.; Everaert, Jonas; Kummerfeld, Erich; Haynos, Ann F.; Vinogradov, Sophia
Abstract: Background: Research indicates that difficulties across multiple socioemotional functioning domains (e.g., social emotion expression/regulation, response to social elicitors of emotion) and negatively biased interpretations of ambiguous social situations may affect eating disorder symptoms. The impact of inflexible interpretations of social situations on eating disorder symptoms is less clear. The present study therefore examined relations between inflexible and biased social interpretations, socioemotional functioning, and eating disorder symptoms. Method: A total of 310 participants from the general population, recruited from an online crowdsourcing platform, completed measures of socioemotional functioning (e.g., rejection sensitivity, negative social exchange), eating disorder symptoms, and positive and negative interpretation bias and inflexibility on a single measurement occasion. Results: Socioemotional functioning impairments (Pillai's trace = 0.11, p  < .001), but not negative ( β  = .07, p =  .162) or positive ( β  = −.01, p =  .804) interpretation bias or inflexible interpretations ( β  = .04, p =  .446), were associated with eating disorder symptoms in multiple regression models. In network analyses controlling statistically for multiple markers of socioemotional functioning, eating disorder symptoms were directly associated with negative (but not positive) interpretation bias. Inflexible interpretations were indirectly linked to symptoms via co‐dampening of positive emotions. Exploratory causal discovery analyses suggested that several socioemotional functioning variables (social anxiety, depression, negative social exchange) may cause eating disorder symptoms. Conclusions: Consistent with cognitive‐interpersonal models of disordered eating, our results suggest that less accurate (biased, inflexible) interpretations of social information contribute to patterns of cognition (anxious anticipation of rejection) and emotion regulation (down‐regulation of positive social emotion) thought to encourage disordered eating. Public Significance: This study suggests that less accurate interpretations of ambiguous social information encourage anxious anticipation of rejection and downregulation of positive social emotions, both of which are thought to promote eating disorder symptoms. Knowledge provided by this study about the likely relations between interpretive processes, social/emotional functioning, and eating disorder symptoms may help inform treatments for eating disorders, particularly those that attempt to modify patterns of interpretation.